Proof: Substitute Two Numbers
Let's prove the following theorem:
if the following are true:
- a = b + c
- b = x
- c = y
then a = x + y
Proof:
Given
1 | a = b + c |
---|---|
2 | b = x |
3 | c = y |
# | Claim | Reason |
---|---|---|
1 | b + c = x + c | if b = x, then b + c = x + c |
2 | x + c = x + y | if c = y, then x + c = x + y |
3 | b + c = x + y | if b + c = x + c and x + c = x + y, then b + c = x + y |
4 | a = x + y | if a = b + c and b + c = x + y, then a = x + y |
Comments
Please log in to add comments